2021
DOI: 10.1515/medgen-2021-2101
|View full text |Cite
|
Sign up to set email alerts
|

Huntington disease update: new insights into the role of repeat instability in disease pathogenesis

Abstract: The causative mutation for Huntington disease (HD), an expanded trinucleotide repeat sequence in the first exon of the huntingtin gene (HTT) is naturally polymorphic and inevitably associated with disease symptoms above 39 CAG repeats. Although symptomatic medical therapies for HD can improve the motor and non-motor symptoms for affected patients, these drugs do not stop the ongoing neurodegeneration and progression of the disease, which results in severe motor and cognitive disability and death. To date, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…The previous line of research also demonstrated that the HD gene is located on chromosomal 4p16 and expresses huntingtin a 348 kDa glycoprotein that is abundantly distributed throughout synapses [ 4 ]. Excitotoxicity, energy deprivation, oxidative damage, inflammatory response, and protein expression are among the mechanisms through which neurodegeneration proceeds in HD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The previous line of research also demonstrated that the HD gene is located on chromosomal 4p16 and expresses huntingtin a 348 kDa glycoprotein that is abundantly distributed throughout synapses [ 4 ]. Excitotoxicity, energy deprivation, oxidative damage, inflammatory response, and protein expression are among the mechanisms through which neurodegeneration proceeds in HD [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Huntington’s disease (HD), accumulating mutant huntingtin protein with an expanded polyglutamine repeat is critical in the disease process [ 105 ]. H 2 S has been shown to influence the aggregation and toxicity of mutant huntingtin, contributing to the degeneration of neurons in the striatum and other brain regions affected in HD.…”
Section: Resultsmentioning
confidence: 99%
“…Huntington's disease (HD) is an inherited progressive neurodegenerative disorder belonging to the polyglutamine disorders ( McColgan and Tabrizi, 2018 ). Polyglutamine disorders share adult onset of symptoms, which include chorea, general motor impairment, psychiatric disorders, and cognitive decline ( Arning and Nguyen, 2021 ). The disease usually begins in midlife, with progressive neurodegeneration leading to death within ten years of onset ( Niemann and Jankovic, 2019 ).…”
Section: Introductionmentioning
confidence: 99%